2016
DOI: 10.1038/srep32455
|View full text |Cite
|
Sign up to set email alerts
|

Open System Tribology and Influence of Weather Condition

Abstract: The tribology of an open system at temperatures ranging between 3 °C and −35 °C, with and without snow, was investigated using a pin-on-disc tribometer mounted in a temperature-controlled environmental chamber. The relationship between the microstructure and ductility of the materials and the tribology at the contacting surfaces was investigated. The study shows that during continuous sliding, pressure causes snow particles to melt into a liquid-like layer, encouraging the generation of oxide flakes on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In some cases, above a certain threshold, the increasing positive charge does not improve antimicrobial activity, which is explained by the fact that an increase in the charge is closely related to the reduced hydrophobicity of peptides (and also the modification of the hydrophobic moment). [16][17][18] AMPs have substantial portions of hydrophobic residues (over 30%), while the ratio of hydrophobic and uncharged residues (e.g. leucine, phenylalanine or tryptophan) to charged amino acids can vary from 1:1 to 2:1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, above a certain threshold, the increasing positive charge does not improve antimicrobial activity, which is explained by the fact that an increase in the charge is closely related to the reduced hydrophobicity of peptides (and also the modification of the hydrophobic moment). [16][17][18] AMPs have substantial portions of hydrophobic residues (over 30%), while the ratio of hydrophobic and uncharged residues (e.g. leucine, phenylalanine or tryptophan) to charged amino acids can vary from 1:1 to 2:1.…”
mentioning
confidence: 99%
“…[3,22] However, to maintain surface activity, at least seven or eight amino acids are needed, [15] while 15-20 amino acids are required to span the membrane in the case of helical peptides. [18] Recent research has revealed that the decreasing chain length of peptides in a certain range retains its high antimicrobial activity by reducing its toxicity. The molecular weights of AMPs are less than 10 kDa and typically in the range of 1-5 kDa.…”
mentioning
confidence: 99%
“…There are some determinant factors that affect the antimicrobial activity of peptides, such as net charge, [49][50][51] hydrophobicity, [52] α-helix propensity, [32] and the length of the peptide. [14] In this study, WL2 and WL3 have stronger antimicrobial activity than WL1, which is mainly due to the α-helical propensity in the membrane environment. The peptides transformed from random conformations in the aqueous environment to amphipathic α-helices, which increase the partition into the membrane and increase the antimicrobial activity.…”
Section: F I G U R Ementioning
confidence: 66%
“…The microbial sample was initially prepared as described for early SEM analysis. [14] The overnight cultures of logarithmic phase E. coli ATCC 25922 and S. aureus ATCC 29213 cells were harvested by centrifuging at 1,000 × g for 10 min, washed twice with PBS, and diluted to an OD 600 of 0.1-0.2. The 1 × MIC peptides were challenged with bacteria at 37°C for 1 hr, and the bacterial growth in PBS was used as control.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
See 1 more Smart Citation